Pendidikan Agama Islam dan Budi Pekerti SD Kelas I dalam Kurikulum 2013 - Ilmi, Binti Wasi'atul (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2014)
The study is intended to exmine if the materials match the themes inthe student book of Pendiddikan Agama Islam dan Budi Pekerti SD Kelas I,and to examine the implementation of scientific approach in the student book ofPendiddikan Agama Islam dan Budi Pekerti SD Kelas I. The results obtained inthis study can be concluded that of the 32 sub-theme material conformity with thetheme seen from the suitability of the curriculum, 0.03% is not fulfilled, from thesuitability of KI and KD 0.09% is not fulfilled, from the suitability of the learningobjectives 0.28% is not fulfilled, from the appropriateness of the contents of eachcolumn 0.37% is partially fulfilled. Then from the application of the scientificapproach of the 32 sub-themes there 26 sub themes using the scientific approachwhile six sub-themes do not use scientific approach with images, 0.5% partiallyfulfilled and there are 0.07% is not fulfilled.